2005
DOI: 10.1007/bf03168451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-hydroxydecanoate and ischemic preconditioning on the ischemic-reperfused heart of fed and fasted rats

Abstract: This investigation aimed to assess whether the mitochondrial ATP-sensitive potassium channel blocker 5-hydroxydecanoate (5-HD) could abolish the protection conferred by fasting and ischemic preconditioning (IPC) and to ascertain whether these effects are associated with glycogen breakdown and glycolytic activity. Langendorff perfused hearts of fed and 24-h fasted rats were exposed to 25 min ischemia plus 30 min reperfusion. IPC was achieved by a 3 min ischemia plus a 5 min reperfusion cycle. 5-HD (100 microM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…This is associated with an improved functional recovery following a period of ischaemia in hearts from fasted rats, as reported previously. [1][2][3][4][5][6] This suggests that the glutathione status of the heart The results of the present study agree with the data of Blaustein et al, 31 who observed that functional recovery was impaired in hearts that had been depleted of glutathione and were exposed to 20 min total global ischaemia. In contrast.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is associated with an improved functional recovery following a period of ischaemia in hearts from fasted rats, as reported previously. [1][2][3][4][5][6] This suggests that the glutathione status of the heart The results of the present study agree with the data of Blaustein et al, 31 who observed that functional recovery was impaired in hearts that had been depleted of glutathione and were exposed to 20 min total global ischaemia. In contrast.…”
Section: Discussionsupporting
confidence: 90%
“…It is likely that this shift of metabolism towards the pentose phosphate pathway also occurs in hearts isolated from fasted rats, because both previously reported and current data indicate that fasting increases the oxidation of fatty acids derived from endogenous TAG and also decreases lactate production. 2,3,6,8 The heart has a large requirement for NADPH, which is needed to maintain the tissue content of GSH in order to counteract the oxidative stress that results mainly from the production of ROS in the mitochondria. Given that the capacity of the oxidative pentose phosphate pathway in the heart is very limited, 38 the myocardium has no efficient system to detoxify oxygen free radicals produced during reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…182 It has been reported that fasting increased the myocardial BHB/AcAc ratio reflecting altered mitochondrial redox state and fasting of rats for only 24 hours improved the post-ischaemic recovery of contractile function and reduced the lactate dehydrogenase release in isolated hearts subjected to global IR. 183 In another study, short-term fasting increased the concentration of BHB and BHB/AcAc ratio compared to controls, limited the infarct size and reduced the total number of premature ventricular complexes and the duration of ventricular tachycardia occurring at early reperfusion. 184 However, low concentration of endogenous ketone bodies failed to preserve the myocardial ATP levels whereas exogenous supplementation (to 40 times the original concentration) prevented the loss of ATP by ischaemic injury.…”
Section: Ketonesmentioning
confidence: 95%